2015
DOI: 10.3892/ijmm.2015.2423
|View full text |Cite
|
Sign up to set email alerts
|

Bovine parathyroid hormone enhances osteoclast bone resorption by modulating V-ATPase through PTH1R

Abstract: The vacuolar-type H+ adenosine triphosphatase (V-ATPase) plays an important role in cellular acidification and bone resorption by osteoclasts. However, the direct effect of bovine parathyroid hormone (bPTH) on V-ATPase has not yet been elucidated. The aim of the present study was to assess the effects of bPTH on V-ATPase and osteoclasts. Osteoclasts from bone marrow (BM)-derived monocytes of C57BL/6 mice were cultured with or without bPTH. The mRNA and protein expression levels of the V-ATPase a3-subunit and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Studies that were done on current treatments of osteoporosis such at BMP2 and PTH showed that long-term usage of these compounds resulted in enhancing osteoclast differentiation and bone resorption [7,29,30]. It could be speculated that long term treatment of osteoporosis using BMP2 and PTH might increase osteoclast differentiation and bone resorption due to the direct and indirect effects (via osteoblasts) on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that were done on current treatments of osteoporosis such at BMP2 and PTH showed that long-term usage of these compounds resulted in enhancing osteoclast differentiation and bone resorption [7,29,30]. It could be speculated that long term treatment of osteoporosis using BMP2 and PTH might increase osteoclast differentiation and bone resorption due to the direct and indirect effects (via osteoblasts) on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing scientific opinion is that only osteoblast-lineage cells possess a PTH receptor, with only a small number of researchers reporting that they are also present on osteoclast-lineage cells. Therefore, this raised osteoclast activity is not through direct action of PTH, but rather an indirect response to altered osteoblast function as continuous PTH raises RANKL and lowers OPG expression, increasing the RANKL:OPG ratio (Dempster et al, 2005 ; O'Brien et al, 2008 ; Silva and Bilezikian, 2015 ; Liu et al, 2016 ).…”
Section: Modulators Of Remodellingmentioning
confidence: 99%
“…In vivo studies have demonstrated that continuous infusion of PTH triggers a decrease of OPG and an increase of RANKL capable of inducing osteoclast differentiation and promoting bone resorption (Ma et al). Another reason for our results would be the increased expression of a3 and d2 subunits of vacuolar-type H + adenosine triphosphatase (V-ATPase), which accelerates intracellular acidification when activated and increases bone resorption capability of osteoclasts (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%